1999
DOI: 10.1177/026988119901300306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of amphetamine on saccadic eye movements in man: possible relevance to schizophrenia?

Abstract: The antisaccade task can be used to test the voluntary control of saccadic eye movements (SEMs). In many disorders with postulated hyperdopaminergic neurotransmission, there are reports of abnormalities in SEMs. To further investigate this, the role of dopamine in SEMs, performance on an antisaccade task was examined in subjects with a history of amphetamine use (a dopamine releaser and reuptake inhibitor). A prospective design was employed in a teaching hospital setting. Six subjects (five males) with a histo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 18 publications
0
10
1
Order By: Relevance
“…It should be noted that antisaccade performance in healthy participants has been found to be sensitive to a number of psychopharmacological manipulations, including lorazepam (Green et al 2000), amphetamine (Dursun et al 1999) and alcohol (Khan et al 2003). However, the effect of these compounds has been to increase correct antisaccade latencies, as opposed to the decrease we found with nicotine and modafinil.…”
Section: Discussioncontrasting
confidence: 72%
See 1 more Smart Citation
“…It should be noted that antisaccade performance in healthy participants has been found to be sensitive to a number of psychopharmacological manipulations, including lorazepam (Green et al 2000), amphetamine (Dursun et al 1999) and alcohol (Khan et al 2003). However, the effect of these compounds has been to increase correct antisaccade latencies, as opposed to the decrease we found with nicotine and modafinil.…”
Section: Discussioncontrasting
confidence: 72%
“…However, Duka and Lupp (1997) reported that levadopa, a drug used to increase synthesis of dopamine in Parkinsons Disease also increased antisaccade errors in healthy, young volunteers. Similarly, Dursun et al (1999) found that amphetamine increased correct antisaccade latency and error rate. At present there are insufficient data to determine whether these apparently conflicting findings are due to differences in methodology, or in fact suggest that there is an optimal level of dopamine required for successful antisaccade performance (c.f.…”
Section: Discussionmentioning
confidence: 85%
“…However, this is the first strong behavioural evidence of such an interaction in humans. Importantly, there was no evidence of saccadic disinhibition, nystagmus or abnormal accuracy or latency of antisaccades that are usually observed in humans who have ingested stimulants that disrupt dopaminergic frontostriatal neural networks (Tedeschi et al, 1983;Hotson et al, 1986;Dursun et al, 1999;Klein et al, 2002;Vassallo and Abel, 2002). The pattern of saccade slowing and dysmetria together with normal saccade latency and normal antisaccades (error rate and latency) that was observed among intoxicated kava users is similarly observed among humans with cerebellar abnormalities due to degenerative ataxic disorders (Moschner et al, 1994;Buttner et al, 1998;Wessel et al, 1998) and among humans and animals with cerebellar lesions (Bötzel et al, 1993;Barash et al, 1999).…”
Section: Discussionmentioning
confidence: 74%
“…It has recently been reported that a simple manual reaction time task is delayed in PD patients as a result of subcutaneous apomorphine injection, a D1 and D2 receptor agonist (Muller et al 2002), and similarly apomorphine has been reported to impair the reaction time in certain strains of rats (Wilcox and Spirduso 1988). Amphetamine causes dopamine release and reuptake inhibition, and has been found to prolong saccadic latencies in humans (Dursun et al 1999), whereas haloperidol, a dopamine antagonist with mild anticholinergic action, has been found not to affect saccades (Lynch et al 1997). …”
Section: The Effect Of L-dopa On Latency Distributionsmentioning
confidence: 99%